The church as a HIV-competent faith community : an assessment of Christian AIDS Bureau for Southern Africa's Churches, Channels of Hope training : original research - Landman, Christina (Verbum et Ecclesia, 2014)
Julian Müller has envisioned the praxis of theology, from a postfoundational point of view, to develop in two movements: engagement in a community that leads to 'real contextual outcomes' and the establishment of new traditions as deconstructed discourses that move beyond single communities. This article assesses the Churches, Channels of Hope (CCoH) training of the Christian AIDS Bureau for Southern Africa (CABSA) in terms of the two criteria laid down by Müller. Firstly, do they successfully train their facilitators to skilfully empower their faith communities to become competent in dealing with people living with HIV? In other words, does the CCoH training lead to 'real contextual outcomes'? Secondly, are the deconstructed social discourses put in place by the CCoH training that focus on the 'new' Christian values of human worthiness and agency able to constitute a contra-culture that will move beyond the boundaries of specific contexts? After the CCoH facilitator's manual and a report on the facilitators' reaction to the training course have been studied, it was found that the CCoH training embodies 'HIV competency' in practices and discourses that can indeed be called 'contextual' as well as 'contra-cultural' although they lack some much-needed skills in reading the Bible from a non-fundamentalist point of view and conducting their impact studies in a more sophisticated and non-reductionist way. Intradisciplinary and/or interdisciplinary implications: The article wants to make a contribution to HIV discoursing over a wide range of disciplines. The lifestyle changes and spiritual healing of the CCoH training that is assessed here inform the fields of counselling, life skills, law and gender. The proposed contra-culture and alternative discourses at stake touch on the fields of primary, secondary and, indeed, tertiary education.
Free